Central bank financial strength and inflation: Is there a robust link? - Perera, Anil; Ralston, Deborah; Wickramanayake, Jayasinghe (Journal of Financial Stability, 2013)
Central bank financial strength has not been a fundamental issue for a substantial period of time. However, recent theoretical and empirical studies argue that central banks need to maintain a sufficient level of financial strength to perform their functions effectively and to achieve monetary policy objectives. In this study, we examine the empirical relationship between central bank financial strength and inflation using an unbalanced panel data set for a sample of selected advanced and emerging countries. We observe a statistically significant and robust negative relationship between central bank financial strength and inflation. This relationship is robust in the presence of other determinants of inflation and for alternative estimation methods. Our results have important implications for policy makers and central bankers. Particularly, our results suggest that avoiding persistent losses and maintaining the health of the central bank balance sheet remain vital pre-conditions for desirable policy outcomes of a central bank.